2002
DOI: 10.1053/jhep.2002.37140
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant monoclonal IgA anti–PDC-E2 autoantibodies derived from patients with PBC

Abstract: Primary biliary cirrhosis (PBC) is an autoimmune liver disease characterized by the presence of autoantibodies to mitochondria (AMA). Recent evidence suggests that PBC develops after a locally driven response in the mucosa, where immunoglobulin A (IgA) is the dominant antibody isotype. In this study, we produced recombinant pyruvate dehydrogenase complex (PDC-E2)-specific dimeric human IgA monoclonal antibodies (mAbs) in a baculovirus expression system. By using 2 anti-PDC-E2 IgG mAbs derived from patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Future studies should focus on the antigen specificity of the IgM and IgG produced in these coronal arrangement-comprising plasma cells. Although IgA transcytosis has been considered one of the contributing factors toward bile duct lesions in PBC, 33,34 it is unlikely that the coronal arrangement we observed in this study includes IgA þ plasma cells. However, we observed that IgA staining was often seen in the degenerated cholangioepithelium of CNSDC or at the apical margin of damaged bile duct cells (data not shown).…”
Section: Discussionmentioning
confidence: 68%
“…Future studies should focus on the antigen specificity of the IgM and IgG produced in these coronal arrangement-comprising plasma cells. Although IgA transcytosis has been considered one of the contributing factors toward bile duct lesions in PBC, 33,34 it is unlikely that the coronal arrangement we observed in this study includes IgA þ plasma cells. However, we observed that IgA staining was often seen in the degenerated cholangioepithelium of CNSDC or at the apical margin of damaged bile duct cells (data not shown).…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, although in PBC subjects the serum AMA is mostly of the IgM and IgG type (39), the biliary AMA is mostly of the IgA isotype (40,41) due to the presence in the ductal epithelium of IgA specific surface receptors that perform the IgA transcytosis (42). These data led to the hypothesis that PBC might develop after a locally AMA IgA driven response in the mucosa (43). We have found that AMA of the IgA isotype are present in the serum of 24% of PBC patients, and that there is a considerable correlation (82%) between the results of the AMA IgA and the anti-tTG IgA tests.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that such apical staining is seen only with selected and not all mAbs that react with PDC‐E2 and that distinct epitopes can be identified with these apically staining mAbs led to the initial hypothesis that a target molecule cross‐reactive with PDC‐E2 could be located at the apical surface of BECs in PBC 57–59. However, subsequent research demonstrated that the apical staining was due to a new complex between AMA of immunoglobulin A (IgA) isotype and PDC‐E2, and this raised the potential role of IgA as a participant in the immune‐mediated destruction of BECs 60, 61…”
Section: The Convenient and Inconvenient Truthsmentioning
confidence: 99%